Propuesta de mejoramiento de procesos constructivos en la construcción del Centro Nacional de Congresos y Convenciones - Badilla-Piedra, Erick (Instituto Tecnológico de Costa Rica, 2017)
The developed theme was the measurement of productivity and its yields in construction processes of the National Center of Congress and Conventions, and the search of a good plan to get improvements. The main objective was to analyze three constructive processes that were selected in the construction work that was made by the construction company EDICA with the purpose to implement tools to help to increase its efficiency and productivity. Different methods were used to make this project such as: field measurement, videotaping, surveys and more information collected with which by tools like flow diagrams, Ishikawa flow, value flow diagrams, methods like Crew Balance and Work Sampling and others with which was possible to know the yields, productivity, displacements, times and more value information for making improvement proposals. The selected processes were the following: the preparation and the placement of wooden framework and concrete subfloor, the welding of roof trusses and its placement in the main room; also, the movement of land and the preparation of the parking. The best productivities were found in the mounting of roof trusses with 64% and the worst in the welding of roof trusses with just the 28%. The measurement shown that the activities carried out with machinery or in the workshop generate better productivities than performed manually. The main recommendations in the improvement plan are mainly guided to have better sizes in the teamwork, avoid unnecessary displacements, the design of the place should be improved and reduce the debris.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2017.
Keywords: Productividad; Rendimiento; Eficiencia; Ingeniería en construcción; Diseño; Research Subject Categories::TECHNOLOGY::Civil engineering and architecture::Building engineering